Measurement of initial-state-final-state radiation interference in the processes e+e- → [mu]+[mu]-γ and e+e- → π+π-γ - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
Charge asymmetry in the processes e+e−→μ+μ−γ and e+e−→π+π−γ is measured using 232 fb−1 of data collected with the BABAR detector at e+e− center-of-mass energies near 10.58 GeV. An observable is introduced and shown to be very robust against detector asymmetries while keeping a large sensitivity to the physical charge asymmetry that results from the interference between initial- and final-state radiation (FSR). The asymmetry is determined as a function of the invariant mass of the final-state tracks from production threshold to a few GeV/c2. It is compared to the expectation from QED for e+e−→μ+μ−γ, and from theoretical models for e+e−→π+π−γ. A clear interference pattern is observed in e+e−→π+π−γ, particularly in the vicinity of the f2(1270) resonance. The inferred rate of lowest-order FSR production is consistent with the QED expectation for e+e−→μ+μ−γ, and is negligibly small for e+e−→π+π−γ.